Classifications and Scores of the Shoulder - Habermeyer, Peter; Magosch, Petra; Lichtenberg, Sven (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This book gives a clearly structured, well-defined compendium of classifications and scores of the shoulder for use in everyday clinical life to improve and simplify the communication between physicians and physiotherapists.